Management of Fetal Dystocia by Partial Fetotomy in Mare - Bawane, Manoj; Ingawale, Maheshkumar; Raulkar, Ratnkar; Kathe, Aboli; Deshmukh, Shyam; Pawshe, Chaitanya (The Indian Journal of Animal Reproduction, 2022)
Delivery of a dead fetus in a mare suffering from dystocia due to right lateral head and neck flexion using partial fetotomy procedure is reported.